2000
DOI: 10.2307/1592546
|View full text |Cite
|
Sign up to set email alerts
|

Chicken Embryo Lethality Assay for Determining the Virulence of Avian Escherichia coli Isolates

Abstract: Multiple isolates of Escherichia coli from clinical cases of colibacillosis and E. coli from the intestinal tracts of normal broilers at slaughter were assayed by the embryo lethality test to determine their virulence. The assay was repeated five times in order to establish reproducibility and determine the statistical parameters of the test. This study showed that the inoculation of approximately 100 colony-forming units in the allantoic cavity of 12-day-old embryos discriminated between virulent and avirulen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
54
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 12 publications
4
54
1
1
Order By: Relevance
“…Microbial infection can cause avian embryo mortality, and bacteria from eggshells and contents of nonviable eggs have been isolated from a range of avian species (10,(33)(34)(35)(36). Our identification of a Neisseria species as the predominant bacterium present in addled eggs appears to be novel, although species in the Neisseria genus have been associated with waterfowl on several occasions.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Microbial infection can cause avian embryo mortality, and bacteria from eggshells and contents of nonviable eggs have been isolated from a range of avian species (10,(33)(34)(35)(36). Our identification of a Neisseria species as the predominant bacterium present in addled eggs appears to be novel, although species in the Neisseria genus have been associated with waterfowl on several occasions.…”
Section: Discussionmentioning
confidence: 83%
“…Inoculating doses were determined through serial dilution and CFU counts; five 10-fold dilutions, beginning with 100 CFU, were prepared from each isolate. Inoculating doses were within ranges reported to have been used by others (32,33,34). One-day-old fertilized White Leghorn chicken eggs obtained from Charles River Laboratories (Wilmington, MA) were incubated at 37°C with high humidity and mechanically tilted to a 45°angle every hour for 7 days prior to infection and throughout the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…The role of the BarA-UvrY TCS in the virulence of APEC strain 7122 was determined using an chicken embryo lethality assay, in which live embryos were infected with a controlled amount of bacteria and were scored as alive or dead by movement of the embryo when held close to a bright light source (12,16,42,69). Mutant strains of 7122 were generated by Red-mediated recombination, with modifications suggested for clinical isolates of E. coli (8,32,38) ( Table 2).…”
mentioning
confidence: 99%
“…It has been shown that APEC proliferates significantly in 6 h postinoculation, causing acute systemic infection or death. 20,21) In our research, the death of infected chickens began from 12 h, and the most benefited doses of XQT decreased the mortality of infected chickens at the death peak during 24 to 48 h after inoculation of APEC. These data suggest that XQT can prevent the porliferation of APEC and the cascade of events induced by APEC or its toxins in vivo.…”
Section: Discussionmentioning
confidence: 53%